Ultralight Three-Dimensional Boron Nitride Foam with Ultralow Permittivity and Superelasticity - Yin, Jun; Li, Xuemei; Zhou, Jianxin; Guo, Wanlin (Nano letters, 2013)
Dielectrics with ultralow permittivity within 2 times that of air, excellent mechanical performance, and high thermal stability are highly attractive to many applications. However, since the finding of silica aerogels in the 1930s, no alternative ultralight porous dielectric with density below 10 mg/cm3 has been developed. Here we present three-dimensional hierarchical boron nitride foam with permittivity of 1.03 times that of air, density of 1.6 mg/cm3, and thermal stability up to 1200 °C obtained by chemical vapor deposition on a nickel foam template. This BN foam exhibits complete recovery after cyclic compression exceeding 70% with permittivity within 1.12 times that of air. Gathering all these exceptional characters, the BN foam should create a breakthrough development of flexible ultralow-permittivity dielectrics and ultralight materials.